Green Innovation: A Meta-Analytic Exploration of Green Supply Chain and Knowledge Sharing Dynamics - Dhani Heryanto Soegieharto; Dini Rosdini; Citra Sukmadilaga (Jurnal Akuntansi dan Keuangan, 2024)
This study investigates the relationship between Green Supply Chain Management (GSCM) and Green Innovation (GI) through a meta-analysis of 24 peer-reviewed studies, addressing gaps in the literature by exploring their interconnectedness across various sectors. The findings reveal a significant positive correlation between GSCM and GI, emphasizing their role in enhancing operational efficiency, environmental sustainability, and competitiveness. A key contribution of this study is the novel integration of learning contexts into the analysis, an area previously underexplored. Furthermore, the research aligns its findings with global sustainability frameworks, such as the Global Reporting Initiative (GRI) and Dow Jones Sustainability Index (DJSI), highlighting the practical implications for environmental reporting, cost management, and risk mitigation. This study advances academic understanding and provides actionable insights for practitioners and policymakers, underscoring the transformative potential of GSCM and GI in driving sustainable innovation and achieving financial and environmental goals.